Synthesis of 3-[2-(1H-imidazol-2-yl)alkyl]-2-thioxo-2,3-dihydroquinazolin-4(1H)-one derivatives - O. A. Zavada; O. V. Tkachenko; I. O. Zhuravel (Zaporozhye State Medical University, 2018)
Abstract Promising biologically active substances are derivatives of imidazole and quinazoline, which are part of the structure of known antifungal drugs and substances with anti-TB and antimicrobial activity. In addition, it should be noted that information on the synthesis and properties of quinoline derivatives containing a fragment of 2-aminoalkylimidazole is practically absent. Proceeding from this, the issue of developing new preparative methods for the synthesis of quinazoline derivatives with a fragment of 2-aminoalkylimidazole appears. Aim. Expanding the synthetic potential of 2-aminoalkilimidazoliv, the study of reactivity and synthesis of new derivatives of 3- [2- (1H-imidazole-2-yl) -alkyl] -2-thioxo-2,3-dyhidrohinazolin-4 (1H)-ones. Materials and methods. Methods of organic synthesis; Physical and physical-chemical methods of analysis of organic compounds (NMR spectroscopy 1H, elemental analysis). Results. The work analyzes the structures that are most promising as potential antimicrobial agents. For the synthesis of new biologically active compounds, we have chosen the strategy of combining quinazoline fragments with an imidazole residue in one molecule. Such an approach, in our opinion, should contribute to increasing the lipophilic properties of the final molecule, which is one of the key requirements for antimicrobial agents. 3-Substituted 2-thioxoquinazolin-4-one was prepared by reacting 2-(α,β-aminoalkyl) imidazoles and with methyl ester of 2-isothiocyanato-benzoic acid. Control of the formation of reaction products was carried out by TCHX. The structure of the 2-thioxoquinazolin-4-one obtained was confirmed by 1H-NMR spectroscopy. The multiplicity and location of the protons are fully consistent with the proposed structure of the compounds. Conclusions. The possibility of using new aminoalkylimidazoles derivatives as an amine component in the reaction of heterocyclicization with o-isothiocyanatoester is investigated. The synthesis of 3- [2- (1H-imidazol-2-yl) -alkyl] -2-thioxo-2,3-dihydroquinazolin-4 (1H) -one was synthesized for the first time.